An integrated analysis of economywide effects of climate change - Hasan Dudu; Erol H. Çakmak (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
The effects of climate change in Turkey are expected to be significant. The aim of this paper is to quantify the effects of climate change on the overall economy by using an integrated framework incorporating a computable general equilibrium model and a crop water requirement model for the period 2010 - 99. The results suggest that the economic effects of climate change will not be significant until the late 2030s; therefore Turkey has a chance to develop appropriate adaptation policies. After the 2030s, the effects of climate change are likely to be significant, with agriculture and food production being the most affected sectors.
Keywords: C68; Q10; Q54; 330; agriculture; climate change; computable general equilibrium; integrated assessment; Turkey